Stigma and mental health of homosexuals in palopo city: a correlation study - Hoesny, Rezkiyah; Alicia L. Tien; Santi, Santi; Munafrin Hoesny (Jurnal Konseling dan Pendidikan, 2025)
This study explores the correlation between stigma and mental health issues among homosexual individuals in Palopo City, Indonesia. Homosexuality remains a highly stigmatized and marginalized subject in many societies, particularly in conservative regions where cultural and religious beliefs influence attitudes towards sexual minorities. The objective of this research is to understand how stigma, both external and internalized, affects the mental well-being of homosexuals in Palopo. Utilizing a qualitative research approach and literature review method, this study examines existing research, case studies, and theories on stigma and mental health in the context of sexual minorities. The findings reveal that homosexual individuals in Palopo experience significant psychological distress due to societal rejection, discrimination, and exclusion. Internalized stigma, characterized by self-hatred and low self-esteem, is prevalent among this group and is linked to various mental health challenges, including depression, anxiety, and suicidal ideation. Moreover, the literature suggests that societal attitudes towards homosexuality in Palopo, influenced by conservative values, exacerbate these mental health issues, leading to a cycle of isolation and poor mental health outcomes. The study also highlights the importance of education, legal reforms, and supportive communities in mitigating stigma and improving mental health outcomes for homosexuals in the region. This research provides valuable insights for policymakers, mental health professionals, and advocacy groups aiming to address the mental health needs of sexual minorities in conservative regions.